L’inclusion De L’éducation À La Santé En Éducation Physique Et Sportive: Représentations Et Contributions Des Enseignants - Abdelaziz Razouki; Fatima Ezzahra Tikouk; Boujemaa Agorram; Sabah Selmaoui; Salah-eddine Khzami (European Scientific Journal, ESJ, 2017)
Physical and Athletic Education (PAE) provide students with knowledge and skills and contributes to their Health Education (HE). Its effects are to be invested outside the school in daily or professional activities and in the practice of physical activities. Health Education is part of a variety of health intervention strategies such as disease prevention and health promotion. In schools, it is presented in several forms and is articulated with several school disciplines. This research focuses on the inclusion of Health Education in Physical and Athletic Education in schools, particularly in secondary schools. It focuses on studying the representations that the teachers of the Physical and Athletic Education in this cycle convey about Health Education and Physical and Athletic Education. It aims to: (1) identify and describe those representations; (2) identify the objectives of the Physical and Athletic Education according to those teachers, and (3) identify the pedagogical approaches that these teachers use to teach Physical and Athletic Education in relation to Health Education. In order to carry out our qualitative, descriptive and exploratory research, we carried out semidirected interviews with ten (10) PAE teachers. Among our salient results is that there is a diversity of representations of teachers in HE education and PAE. On the other hand, majority of these teachers stated the need to mobilize the PAE to contribute to pupil’s HE. The results also show that their pedagogical practices are out of step with the prospect of the inclusion of HE in the field of PAE.